Toward a Theology of Church Division: Carl Braaten and Ephraim Radner in Dialogue - Kemp, Matthew (Ecclesiology, 2019)
Visible divisions between Christians undercut any theological claim of the church's unity. Ecclesiology often neglects this disunity as a subject for theological reflection, instead defaulting to either a triumphalist account of a single ecclesial body or a spiritualized, invisible' unity. Both approaches ultimately avoid, and thus perpetuate, the problem. As a corrective to these trends, this paper considers two theologians who have taken the problem seriously: Carl Braaten and Ephraim Radner. Braaten interprets the Reformation as a renewal movement within the one church, and thus sees denominationalism as a temporary situation which must be directed toward renewal and reunion. Radner argues that the present divisions undermine the legitimacy of all churches, and seeks an ecclesiology that moves beyond any justification of these divisions. By putting Braaten and Radner in conversation, this essay puts forward six insights drawn from both that contribute to deepening theological reflection on church division.